2021
DOI: 10.1155/2021/9917694
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Clinicopathological Characteristics of Papillary Thyroid Carcinoma between Symptomatic and Asymptomatic Patients with Primary Hyperparathyroidism

Abstract: Background. Popularization of cervical ultrasound led to higher detection of papillary thyroid carcinoma (PTC) and primary hyperparathyroidism (PHPT), as well as increasing percentage of asymptomatic PHPT in China. Although the coexistence of PTC and PHPT has been reported, it is unknown whether the clinicopathological features of PTC differ between asymptomatic and symptomatic PHPT patients. Methods. We retrospectively reviewed the medical records of 304 PHPT patients treated in our hospital between January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Some researchers believe that PTC in PHPT cases is overdiagnosed because in PHPT patients with concomitant PTC, the tumor diameter is significantly smaller than in patients with PTC alone ( 39 , 40 ). However, in our previous study, we found that PTC in aPHPT patients showed a higher rate of microscopic extrathyroidal invasion than PTC in the general population ( 41 ). Therefore, the relationship between these two diseases needs further investigation.…”
Section: Discussionmentioning
confidence: 73%
“…Some researchers believe that PTC in PHPT cases is overdiagnosed because in PHPT patients with concomitant PTC, the tumor diameter is significantly smaller than in patients with PTC alone ( 39 , 40 ). However, in our previous study, we found that PTC in aPHPT patients showed a higher rate of microscopic extrathyroidal invasion than PTC in the general population ( 41 ). Therefore, the relationship between these two diseases needs further investigation.…”
Section: Discussionmentioning
confidence: 73%
“…Conversely, in another study conducted with a similar population, decreased serum PTH measurements were obtained for patients with both PHPT and PTC in comparison to patients diagnosed with benign thyroid lesions (26). In another study conducted with 155 patients, a significant inverse association was identified between nonmedullary thyroid carcinoma and levels of preoperative serum Ca in cases of PHPT, similarly to the research reported by Liu et al (6,26). Contrary to those findings, our study, conducted with a much larger patient population compared to previous studies, showed that high serum Ca levels and advanced age were independent risk factors for PTC.…”
Section: Discussionmentioning
confidence: 84%
“…In a study conducted with 318 patients, moderate elevations of serum PTH independently predicted thyroid cancer among patients with PHPT (25). Conversely, in another study conducted with a similar population, decreased serum PTH measurements were obtained for patients with both PHPT and PTC in comparison to patients diagnosed with benign thyroid lesions (26). In another study conducted with 155 patients, a significant inverse association was identified between nonmedullary thyroid carcinoma and levels of preoperative serum Ca in cases of PHPT, similarly to the research reported by Liu et al (6,26).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Liu and coll. (2021) [ 18 ] Showed the higher prevalence of thyroid nodules in asymptomatic PHPT patients and the occurrence of PTC in a considerable percentage of these patients. The study also observed differences in the pathological features of PTC between the two groups, particularly a higher rate of microscopic extrathyroidal invasion in the concomitant PTC among asymptomatic PHPT patients.…”
Section: Resultsmentioning
confidence: 99%